Examination of Infection parameters for Replication of Israeli Isolate of Koi Herpesvirus in Common Carp Brain Cells - Jordan, Lisa; Amtmann, Anette; Heidenreich, Elke; Christian, Juergen; Buchholz, Rainer; Becker, Anna (Journal of Virology and Antiviral Research, 2017)
Research on koi herpesvirus (KHV) is mainly focused on fish trials for the investigation of virus entry, disease progress and immunological responses within the organism in order to develop new diagnostic and treatment strategies. However, examination of in vitro-replication of KHV might give useful insights supporting the understanding of this pathogen as well as contributing to the development of new methods for diagnostic purposes and/or vaccine development. Nevertheless, until today, only few studies have been published on this matter. Thus, this work concerns investigation of in vitro-replication of the Israeli isolate of KHV, KHV-I, in the widely used common carp brain cells (CCB) to identify the parameters leading to high-quality virus stock with high titers for further applications. Therefore, the propagation of the KHV-I at the influence of various cell densities at inoculation, virus load and time of harvest on the propagation of KHV-I was examined. Obtained results indicate that inoculation with relatively high cell densities is advantageous since the highest titers could be reached for 60 000 and 75 000 cells/cm2 already 3 days after inoculation. In contrast, the use of too high virus load for inoculation with too low cell density can result in much lower maximum or even decrease in virus titers. While viral DNA showed to be relatively stable after reaching the maximum, the infectivity of the virus can decrease shortly after the peak. Therefore, selection of the right combination of infection parameters is crucial for reaching the appointed goal. This work gives valuable insights into the replication of KHV-I in CCB cells and indicates the differences between various KHV isolates regarding in vitro-propagation.
Keywords: Common carp brain cells; Koi herpesvirus; Multiplicity of infection; Time of infection; Time of harvest; Replication; Virus titer